The role of Development Finance Institutions (DFIs) in economic growth in Zambia - Kang’ombe, Mutale Matthew (Research of GSB, 2019)
This study empirically investigates the role Development Finance Institutions (DFIs) play in the economic growth of Zambia from 1992: Q1 to 2015: Q4. The main aim of the study is to find out if DFIs enhance economic growth in Zambia and if the growth witnessed over the study period was in fact improved by these inflows. Additionally, a multiple regression is run against the exchange rate, inflation unemployment and interest rate to further analyse the interaction of these variables with DFI inflows and how they have impacted the growth levels experienced in Zambia. The findings show that the impact DFIs on the GDP are ambiguous. In current period and DFI lagged to 2 periods prior, has a depressing effect whilst DFI lagged one period has an encouraging effect on GDP levels. Furthermore, from the cointegration tests, it is evident that there is a long run relationship that exists, signifying that the positive effects of DFIs can be felt in future periods especially if deployed to key sectors. The regression results of the other variables are in line with macro-economic theory which suggests that DFI inflows need to be supplemented with stable macro conditions to boost the degree of positive impact on GDP. To ensure future benefit to Zambia from DFI inflows; recommendations preferred to authorities inferred from the findings include, directing of these funds to job and revenue generating sectors that can increase export revenue. These sectors may include agriculture and manufacturing. Furthermore, it is cardinal that institutional infrastructures are put in place that effect legal and monitoring framework to ensure efficient deployment of these funds within the economy.